Deciphering Human Leukocyte Antigen Susceptibility Maps From Immunopeptidomics Characterization in Oncology and Infections - Juanes-Velasco, Pablo; Landeira-Viñuela, Alicia; Acebes-Fernandez, Vanessa; Hernández, Ángela-Patricia; Garcia-Vaquero, Marina L.; Arias-Hidalgo, Carlota; Bareke, Halin; Montalvillo, Enrique; Gongora, Rafael; Fuentes, Manuel (Frontiers in Cellular and Infection Microbiology, 2021)
Genetic variability across the three major histocompatibility complex (MHC) class I genes (human leukocyte antigen [HLA] A, B, and C) may affect susceptibility to many diseases such as cancer, auto-immune or infectious diseases. Individual genetic variation may help to explain different immune responses to microorganisms across a population. HLA typing can be fast and inexpensive; however, deciphering peptides loaded on MHC-I and II which are presented to T cells, require the design and development of high-sensitivity methodological approaches and subsequently databases. Hence, these novel strategies and databases could help in the generation of vaccines using these potential immunogenic peptides and in identifying high-risk HLA types to be prioritized for vaccination programs. Herein, the recent developments and approaches, in this field, focusing on the identification of immunogenic peptides have been reviewed and the next steps to promote their translation into biomedical and clinical practice are discussed.